Conventional Cartilaginous Tumors: Evaluation and Treatment. Issue 5 (May 2021) - Wells, Matthew E.; Eckhoff, Michael D.; Kafchinski, Lisa A.; Polfer, Elizabeth M.; Potter, Benjamin K.
Abstract : Enchondromas are benign cartilaginous lesions that rarely require surgical intervention. Atypical cartilaginous tumors (ACTs), also referred to as grade-1 chondrosarcomas, may be managed without any intervention or with extended intralesional curettage and bone-void filling. High-grade chondrosarcomas, or grade-2 and 3 chondrosarcomas, should be managed aggressively with wide resection. Chemotherapy and radiation do not currently play a role in the treatment of chondrosarcomas. Differentiating an enchondroma from an ACT and an ACT from a high-grade chondrosarcoma can be difficult and requires clinical experience, radiographic and advanced imaging, and possibly a biopsy. Ultimately, a multidisciplinary team that includes a musculoskeletal oncologist, a radiologist, and a pathologist is needed to make the most appropriate diagnosis and treatment plan for each patient.